2016
DOI: 10.1016/s0140-6736(16)31921-3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and impact of a reduced infant schedule of 4CMenB vaccine against group B meningococcal disease in England: a national observational cohort study

Abstract: Public Health England.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
211
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 250 publications
(222 citation statements)
references
References 17 publications
5
211
1
5
Order By: Relevance
“…However, continued surveillance is vital. Multicomponent MenB vaccine 4CMenB (Bexsero, Basel, Switzerland) was added to the UK national infant vaccination program for infants in September 2015 ( 12 ). Unlike conjugated polysaccharide meningococcal vaccines, 4CMenB is not capsule specific and has the potential to offer broader protection against all meningococcal strains.…”
Section: Discussionmentioning
confidence: 99%
“…However, continued surveillance is vital. Multicomponent MenB vaccine 4CMenB (Bexsero, Basel, Switzerland) was added to the UK national infant vaccination program for infants in September 2015 ( 12 ). Unlike conjugated polysaccharide meningococcal vaccines, 4CMenB is not capsule specific and has the potential to offer broader protection against all meningococcal strains.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the first 10 months of the United Kingdom's implementation of Bexsero Ò were presented; Bexsero Ò was shown to have high vaccine effectiveness (83%) and no safety concerns were observed. 13 The new-generation MenB vaccines have the potential to replace outer membrane vesicle vaccines in epidemic settings.…”
Section: Meningococcal Vaccines Meningococcal Plain Polysaccharide Anmentioning
confidence: 99%
“…As the vaccine was approved based on serological criteria rather than evidence of direct protection, this offered the first opportunity to evaluate its impact against antigenically diverse meningococci responsible for endemic disease and to identify rare adverse events in a large population (27). Ten months after the start of this immunization program, Parikh and colleagues at Public Health England analyzed the initial impact of Bexsero in vaccine-eligible infants using the screening method and showed that effectiveness prior to administration of the booster dose was 82.9% (95% confidence interval [CI], 24.1 to 95.2%) against all MenB cases (28). Compared with the average incidence rate ratio (IRR), estimated in children of the same age during the 4 years prior to the introduction of the vaccine, there was a 50% reduction in cases of MenB disease, i.e., 37 cases compared with a previous average of 74 cases (relative IRR, 0.50; 95% CI, 0.36 to 0.71) in the vaccine-eligible cohort.…”
Section: Vaccines For Protection Against Serogroup B Meningococcimentioning
confidence: 99%